Evaluating the impact of budgetary control on the performance of MDA's in Bauchi state Nigeria: Case study of ministry of budget and planning - Garba, Illiya; Gambo, Isah (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
This study evaluate the impact of budgetary control on the performance of MDA's in Bauchi state was conducted using ministry of budget and planning as a case study. Spearman's rank correlation statistical tools were employed for data analysis. Cognitive evaluation theory is used for the study, which suggests that when looking at a task, we evaluate in term of how well it meets over needs to feel in competent and in control. Finding of the hypotheses tested and the direct interview conducted reveals that planning, goal recognition and accountability all had strong positive relationship on the performance of MDA's in Bauchi State. The results show that there is positive relationship between all the tested hypotheses under discussion. The paper recommend that, organizations should give more impetus to planning as it is the bases of most progress that most organization. Managers are to be proactive as it is what is required in planning and since budgeting and budgetary control contribute to the improvement of management efficiency and high productivity, the budget committee should be educated in the implementation of budget. Thus a budget education should be conducted at least once a year by the financial or independence accounting or management consulting firm. Its usefulness cannot be question or over emphasized.
Keywords: Bauchi; Budget; Control; Performance; Nigeria